Co-culturing with Streptococcus anginosus alters Staphylococcus aureus transcriptome when exposed to tonsillar cells - Bastakoti, Srijana; Pesonen, Maiju; Ajayi, Clement; Julin, Kjersti; Corander, Jukka; Johannessen, Mona; Hanssen, Anne-Merethe (Frontiers in Cellular and Infection Microbiology, 2024)
Improved understanding of Staphylococcus aureus throat colonization in the presence of other co-existing microbes is important for mapping S. aureus adaptation to the human throat, and recurrence of infection. Here, we explore the responses triggered by the encounter between two common throat bacteria, S. aureus and Streptococcus anginosus, to identify genes in S. aureus that are important for colonization in the presence of human tonsillar epithelial cells and S. anginosus, and further compare this transcriptome with the genes expressed in S. aureus as only bacterium. We performed an in vitro co-culture experiment followed by RNA sequencing to identify interaction-induced transcriptional alterations and differentially expressed genes (DEGs), followed by gene enrichment analysis. A total of 332 and 279 significantly expressed genes with p-value < 0.05 and Log2 fold change (log2FC) > |2| were identified in S. aureus after 1 h and 3 h co-culturing, respectively. Alterations in expression of various S. aureus survival factors were observed when co-cultured with S.anginosus and tonsillar cells. The serine-aspartate repeat-containing protein D (sdrD) involved in adhesion, was for example highly upregulated in S. aureus during co-culturing with S. anginosus compared to S. aureus grown in the absence of S. anginosus, especially at 3 h.Several virulence genes encoding secreted proteins were also highly upregulated only when S. aureus was co-cultured with S. anginosus and tonsillar cells, and iron does not appear to be a limiting factor in this environment. These findings may be useful for the development of interventions against S. aureus throat colonization and could be further investigated to decipher the roles of the identified genes in the host immune response in context of a throat commensal landscape.